Glutathione Reductase Is Inhibited by Acetaminophen-glutathione Conjugate In Vitro - Pařík, Patrik; Roušar, Tomáš; Kučera, Otto; Bartoš, Martin; Červinková, Zuzana (Elsevier, 2010)
Acetaminophen is one of commonly used analgesics and antipyretics. It is a safe drug at therapeutic doses but in the overdose, it causes liver injury which may lead to acute liver failure. The aim of the present work was to investigate a new mechanism contributing to the toxic acting of acetaminophen especially to explore the possible inhibition of glutathione reductase through an acetaminophen-glutathion conjugate. The acetaminophen-glutathione conjugate was synthesized by the reaction between glutathione and N-acetyl p-benzoquinone imine and purified by column chromatography. The inhibition effect of the conjugate on two types of glutathione reductase (from yeasts and rat hepatocytes) was tested spectrophotometrically. We synthesized the conjugate and found that the enzyme activity was reduced significantly after treatment with different concentrations of acetaminophenglutathione conjugate in both yeast and hepatocyte glutathione reductases (0.014 U/ml); the enzyme activity (from hepatocytes) was decreased to 79±7 %, 67±2 % and 39±7 %, in 0.37, 1.48 and 3.7 mM concentration of the conjugate, respectively. We found that glutathione reductase was dose-dependently inhibited by the conjugate of acetaminophen and glutathione. Our finding results in new consequences in description of acetaminophen toxicity and, in addition, explains previously published findings which have not been fully explainable till now.
Keywords: acetaminophen toxicity; glutathione reductase; glutathione; hepatotoxicity